Phytoconstituents assessment and toxicity study of Gelidium spinosum water extract in zebrafish (Danio rerio) embryos - Warsi, Warsi; Jaswir, Irwandi; Khatib, Alfi; Ahmed, Qamar Uddin; Mohd. Nawi, Mohamed Sufian; Ahda, Mustofa; Rohman, Abdul; Ardini, Yunita Dewi (Rasayan Journal, India, 2023)
Gelidium spinosum belongs to red seaweed that is used as a food ingredient to heal a variety of diseases. Awareness about the potential medicinal value and actual research data on this plant's toxic effect is currently insufficient. Hence, the current study aimed to determine phytoconstituents using Gas Chromatography-Mass Spectrometry (GC-MS), and investigated the toxic effect of Gelidium spinosum Water Extract (GsWE) using zebrafish (Danio rerio) embryos model. Results of the identification confirmed some known phytoconstituents including alkaloid, cinnamic acid ester, heterocyclic aromatic, organic fatty acids, fatty alcohol, and sugars. Results of a toxicity study of GsWE showed a concentration-dependent increase in mortality and yolk size, meanwhile a decrease in eye size, body length, and heartbeat rate on zebrafish embryos. The median lethal concentration (LC50) of GsWE was obtained at 707.38 mg/L. It was considered in the safe category. GsWE did not affect to zebrafish embryo development at low concentrations. In high concentrations, zebrafish embryos showed abnormalities, such as loss of pigmentation, pericardial oedema, and yolk oedema. The results of this investigation will contribute to reinforcing the safety of G. spinosum-related food supplement manufacturing.